2006
DOI: 10.1016/j.molcel.2006.01.033
|View full text |Cite
|
Sign up to set email alerts
|

XIAP Is a Copper Binding Protein Deregulated in Wilson's Disease and Other Copper Toxicosis Disorders

Abstract: X-linked inhibitor of apoptosis (XIAP), known primarily for its caspase inhibitory properties, has recently been shown to interact with and regulate the levels of COMMD1, a protein associated with a form of canine copper toxicosis. Here, we describe a role for XIAP in copper metabolism. We find that XIAP levels are greatly reduced by intracellular copper accumulation in Wilson's disease and other copper toxicosis disorders and in cells cultured under high copper conditions. Elevated copper levels result in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 40 publications
3
114
2
5
Order By: Relevance
“…In this context, of particular importance is the evidence that an X-linked inhibitor of apoptosis (XIAP), known primarily for its caspase inhibitory properties, plays a role in copper metabolism (40). Indeed, it has been demonstrated that XIAP efficiently binds copper, a process that accelerates its degradation and decreases its ability to inhibit caspase-3.…”
Section: Redox-responsive Anti-apoptotic Proteins: Key Components Of mentioning
confidence: 99%
“…In this context, of particular importance is the evidence that an X-linked inhibitor of apoptosis (XIAP), known primarily for its caspase inhibitory properties, plays a role in copper metabolism (40). Indeed, it has been demonstrated that XIAP efficiently binds copper, a process that accelerates its degradation and decreases its ability to inhibit caspase-3.…”
Section: Redox-responsive Anti-apoptotic Proteins: Key Components Of mentioning
confidence: 99%
“…32,33 This form of XIAP has reduced ability to interact with caspases and increased rates of cell death in response to apoptotic stimuli. 33 Since XIAP has been suggested to be a modulator of NFκB activity, 34,35 we hypothesized that changes in XIAP may account for the copper-dependent defects in NFκB activation. Addition Figure 4.…”
Section: Inhibition Of Nfκb By Copper Is Independent Of Copper's Effementioning
confidence: 99%
“…In addition to playing an important role in copper homeostasis, more recent studies demonstrated that intracellular copper levels in turn regulate XIAP [30]. Besides its known ability to bind zinc [9,73,74], XIAP was found to be a strong copper binding protein.…”
Section: Xiap and Coppermentioning
confidence: 99%
“…By directing COMMD1 for proteasomal degradation, XIAP promotes copper retention in various models including cultured cells and Xiap deficient mice [29]. In addition to this role in copper homeostasis, XIAP turns out to be a copper binding protein whose intracellular levels and antiapoptotic actions are negatively regulated by intracellular copper [30]. Therefore, by this model, copper itself provides negative feedback to the actions of XIAP within the intracellular environment.…”
Section: Introductionmentioning
confidence: 99%